Mammillaria breviplumosa (Cactaceae, Cacteae), a new species from Mexico - García-Morales, Leccinum J.; Ramírez-Chaparro, Ricardo; Sigala-Chávez, Alejandro; Iamonico, Duilio (Phytotaxa, 2020)
A new species of Mammillaria, named Mammillaria breviplumosa, is described from Mexico (Durango, Municipality of Mapimí). It is morphologically very similar to M. sanchez-mejoradae. Diagnostic features of the proposed new species are the cylindrical and apically truncate tubercles, the embedded fruits, the white-magenta striped perianth segments, the small feather-like spines and the helicoidal arrangement of the tubercles on the stem. A diagnostic key for the closest species of Mammillaria occurring in northern Mexico is proposed.